Spodoptera albula susceptibility to Bacillus thuringiensis-based biopesticides - Goncalves, Kelly Cristina [UNESP]; Boica Junior, Arlindo Leal [UNESP]; Duarte, Rogerio Teixeira; Moreira, Lais Fernanda [UNESP]; Nascimento, Joacir do [UNESP]; Polanczyk, Ricardo Antonio [UNESP] (Elsevier B.V., 2018)
Single concentration and virulence (mean lethal concentration) bioassays were performed to evaluate the susceptibility of S. albula second instar larvae to seven Bacillus thuringiensis-based biopesticides. Bioassays were conducted using three replicates and repeated three times at 25 degrees C, 70 +/- 10% RH, and a 12:12 (light/dark) photoperiod; mortality was recorded seven days after treatment. The results were subjected to a Tukey's test and Probit analysis. Agree, DiPel SC, and XenTari achieved mortality rates of up to 80%, with the first of these being the most virulent against S. albula. Different Dipel formulations showed different degrees of larvicidal activity.
Keywords: Microbialcontrol; Gray-streaked armyworm moth; Pest management